Unilib - Arifin, Nur Farzana; Mohsin, Alya Amirah; Mohd Tahir, Noor Fathinie; Md Rosli Shanarat, Nurul Elina; Tengku Dzulkifli, Tengku Nur Nadhirah; Idris, Sufy Rabea Adawiya (Universiti Teknologi MARA, Kedah, 2019)
Access to information is a fundamental human right that can break the cycle of poverty and support sustainable development. The library is the only place in many communities where people can access information that will help improve their education, develop new skills, find jobs, build businesses, make informed agricultural and health decisions, or gain insights into environmental issues. Their unique roles make libraries important development partners, both by providing access to information in all formats and by delivering services and programs that meet the needs for information in a changing and increasingly complex society. (IFLA Statement on Libraries and Development, 2017). PTAR's mobile application, known as UiTM Library Mobile Apps is a collaborative in-house development between PTAR and UiTM Digital Campus (DC) Developers team since May 2018. This project has focused on three (3) features to be added as an improvement of the current “UiTM Library Apps". These three features are “Buy N Sell”, “Self-Collect & Delivery” & “e-Dictionary”. The main purpose is to solve the problems such as time constraints, transportation and health faced by users and simultaneously will assist the users of the PTAR library to use library resources and services. These features are proposed due to the needs of the staff and students. Thus, with the existence of these new features and improved version of UiTM Library application, it can help UiTM users to ease the access of information.